1985
DOI: 10.1119/1.14132
|View full text |Cite
|
Sign up to set email alerts
|

Relativistic one-dimensional hydrogen atom

Abstract: Equivalence between focused paraxial beams and the quantum harmonic oscillator Am. J. Phys. 73, 625 (2005) Elementary Quantum Mechanics in One Dimension Am. J. Phys. 73, 480 (2005) The wave function and reality Am. J. Phys. 73, 197 (2005) Quantum harmonic oscillator revisited: A Fourier transform approach Am.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
32
1
3

Year Published

1996
1996
2014
2014

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(38 citation statements)
references
References 0 publications
2
32
1
3
Order By: Relevance
“…The results obtained after solving the Klein-Gordon equation apply to an electron without spin. The advantage of this approach [15] can be easily understood if we recall that the Schödinger equation does not take into account the spin of the electron (1) and then we can directly compare the relativistic and nonrelativistic energy spectra.…”
Section: Relativistic Hydrogen Atommentioning
confidence: 99%
See 1 more Smart Citation
“…The results obtained after solving the Klein-Gordon equation apply to an electron without spin. The advantage of this approach [15] can be easily understood if we recall that the Schödinger equation does not take into account the spin of the electron (1) and then we can directly compare the relativistic and nonrelativistic energy spectra.…”
Section: Relativistic Hydrogen Atommentioning
confidence: 99%
“…A less studied problem is that of a relativistic 2D hydrogen atom in a magnetic field. Perhaps relativistic effects are not very important in semi-conducting devices but nevertheless they cannot be neglected when the interacting potentials are strong [14,15]. Recently, the importance of considering relativistic effects has been pointed out when one computes the energy levels of semiconductors in high magnetic fields [16].…”
Section: Introductionmentioning
confidence: 99%
“…The analogous relativistic problem [12][13][14], as governed by Dirac's equation, is equally fascinating, and likewise, the problem has also been investigated in low dimensions, both in two dimensions [15,16] and in one dimension [17][18][19]. The rise of Dirac materials [20], condensed matter systems with quasiparticles welldescribed by the Dirac equation, has led to revisits of Dirac-Kepler problems with Dirac-like matrix Hamiltonians.…”
Section: Introductionmentioning
confidence: 99%
“…This problem was also analyzed with the Klein-Gordon equation for a Lorentz vector coupling. 24,25 By using the technique of continuous dimensionality, the problem was approached with the Schrödinger, Klein-Gordon, and Dirac equations. 26 In this last work, it was concluded that the Klein-Gordon equation, with the interacting potential considered as a time component of a vector, provides unacceptable solutions while the Dirac equation has no bounded solutions at all.…”
Section: Introductionmentioning
confidence: 99%